2005
DOI: 10.1002/zaac.200570027
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Spinel‐Type Gallia‐Alumina Solid Solutions

Abstract: By precipitation with ammonia of ethanolic solutions containing the appropriate proportions of gallium and aluminium nitrate, following by calcination of the resulting gels at 773 K, mixed Ga 2 O 3 /Al 2 O 3 oxides having Ga:Al ratios of 9:1, 4:1, 1:1, 1:4 and 1:9 were obtained. Powder X-ray diffraction showed that these mixed metal oxides form a series of solid solutions having the spinel-type structure; also shown by γ-Al 2 O 3 and γ-Ga 2 O 3 . The specific surface area (determined by nitrogen adsorption at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 53 publications
6
34
0
Order By: Relevance
“…Taking both yield of propylene and the catalyst stability into account, 773 K could be the most appropriate temperature for the propane dehydrogenation reaction over Ga 2 O 3 -Al 2 O 3 mixed oxides. a-, b-, and d-Ga 2 O 3 , are known to be present depending upon the treatment conditions [24,25]. It also can be observed that the diffraction peaks were rather broad that suggested a poor crystallinity nature of the mixed oxide samples, which has already been reported to be a common feature of the metastable c-variety of both alumina and gallia polymorphs [24,25].…”
Section: Catalytic Dehydrogenation Of Propanementioning
confidence: 91%
See 3 more Smart Citations
“…Taking both yield of propylene and the catalyst stability into account, 773 K could be the most appropriate temperature for the propane dehydrogenation reaction over Ga 2 O 3 -Al 2 O 3 mixed oxides. a-, b-, and d-Ga 2 O 3 , are known to be present depending upon the treatment conditions [24,25]. It also can be observed that the diffraction peaks were rather broad that suggested a poor crystallinity nature of the mixed oxide samples, which has already been reported to be a common feature of the metastable c-variety of both alumina and gallia polymorphs [24,25].…”
Section: Catalytic Dehydrogenation Of Propanementioning
confidence: 91%
“…Broadness notwithstanding, the diffraction maxima evidenced in the XRD patterns of the gallia-alumina samples could be assigned to a single phase having the cubic spineltype structure (space group Fd3m) [24] as shown by the indexing in Fig. 4.…”
Section: Catalyst Characterizationmentioning
confidence: 97%
See 2 more Smart Citations
“…Gallium oxide-based materials have attracted considerable attentions, and they have been applied for catalysts [3][4][5][6], gas sensors [7,8], phosphors [9], spintronics devices [10], and transparent electronic devices [11]. The studies on the formation and properties of gallium oxide-based materials have been conducted using various synthesis methods, e.g., coprecipitation [12], solvolysis of GaCl 3 in N, N-dimethylformamide [13], pulsed-laser deposition technique [14], calcination of gels [15], hydrothermal method [16], solvothermal or glycothermal technique [17,18], and colloidal synthesis route [19,20]. The catalytic properties of copper-doped gallium oxide with spinel-type structure formed through microwave hydrothermal method have been reported, but its crystallinity was very low [21].…”
Section: Introductionmentioning
confidence: 99%